Cytohistologic correlation of basaloid salivary gland neoplasms: Can cytomorphologic classification be used to diagnose and grade these tumors?. Issue 2 (19th November 2019) - Gargano, Stacey M.; Sebastiano, Christopher; Solomides, Charalambos C.; Griffith, Christopher C.; HooKim, Kim
Abstract : Background: Basaloid salivary gland neoplasms (BSNs), which include benign primary tumors and primary or metastatic malignancies, show overlapping morphology in fine‐needle aspiration (FNA). The Milan system recommends assigning a grade (low or high) to malignant salivary neoplasms because of the impact on surgical planning. This study investigated cytomorphologic features of BSNs on FNA that would help to favor a high‐grade malignancy over a low‐grade malignancy or a benign tumor. Methods: Two pathologists performed a double‐blinded cytologic evaluation of FNA cases diagnosed as BSNs that had corresponding surgical resections. The diagnosis made with the Milan system was correlated with the final surgical diagnosis and grade. Cytologic sensitivity, specificity, and predictive values were calculated. Results: There were 132 BSN FNA cases; cytology slides were available for 77 of 87 patients who had undergone resection. The risk of malignancy for the benign neoplasm (BN), salivary gland neoplasm of uncertain malignant potential (SUMP), suspicious for malignancy (SFM), and malignant categories were 13.6%, 22%, 100%, and 100%, respectively. The sensitivity of the malignant/SFM category was 51.7%; another 37.9% of confirmed malignancies were diagnosed as SUMP. The specificity of the BN category was 86%. Favoring a high‐grade malignancy on FNA had 100% accuracy (5 of 5). Favoring a low‐grade malignancy on FNA had 75% accuracy (6 of 8). The most specific cytomorphologic clues for a high‐grade malignancy were necrotic/apoptotic debris, mitoses, discohesion, and anisonucleosis. Conclusions: BSNs encompass a broad spectrum of primary and metastatic tumors. Necrotic/apoptotic debris, mitotic activity, discohesion, and significant anisonucleosis, alone or especially in combination, should make a cytopathologist suspect a high‐grade malignancy. Abstract : Distinguishing between benign and malignant primary and secondary basaloid tumors in the salivary gland is challenging because these tumors tend to show overlapping morphology in fine‐needle aspiration. Necrotic/apoptotic debris, mitotic activity, discohesion, and anisonucleosis, alone or especially in combination, are helpful features for diagnosing high‐grade basaloid malignancies, and this may aid surgical management.